The effects of residence duration in high background radiation areas on immune surveillance - Borzoueisileh, Sajad (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: The effective dose received by humans from natural sources is about 2.4 mSv y(-1), but this is 10.2 mSv y(-1) for inhabitants of Ramsar, a city in northern Iran. Carcinogenesis is one of the most studied effects of radiation, especially in high doses. Nonetheless carcinogenesis of low doses is uncertain. A recent epidemiological study in high background radiation areas of Ramsar showed that the cancer incidence in this era is lower than neighbors. The reason of this different behavior is under study yet. NK cells, helper, and Cytotoxic T cells are most important components of the tumor immune surveillance. The counts and activities of these cells and also leukocytes, lymphocyte, neutrophil cells, and other important parameters were studied in the residents of Ramsar with different duration of exposure to chronic low dose radiation. MATERIALS AND METHODS: Fifty residents of high background radiation areas, who were between 25 and 35 years and fully healthy, were selected randomly and their consent was obtained. Then, 2 cc fresh peripheral bloods were taken in sterile conditions. Complete blood cell counts were performed by an automatic hematology analyzer and CD4+, CD8+, NK, and CD107a+ cell counts were determined by monoclonal antibodies and flowcytometry. CD4+ and CD8+ percentages and the CD4/CD8 ratio were determined and the data were analyzed using SPSS 16. RESULTS: The percentages of CD4+ cells increase, but the counts of CD107a+ cells decline in higher exposure durations. The other parameters did not have significant regression with exposure duration. CONCLUSIONS: These confirm that living in high background radiation areas may induce changes in the immune system gradually and address more investigations.